2023
DOI: 10.1038/s41598-022-24373-5
|View full text |Cite
|
Sign up to set email alerts
|

Geographical variability of bacterial communities of cryoconite holes of Andean glaciers

Abstract: Cryoconite holes, ponds full of melting water with sediment on the bottom, are hotspots of biodiversity on glacier surfaces and host dynamic micro-ecosystems. They have been extensively investigated in different areas of the world (e.g., the Arctic, Antarctic, Alps, and Himalaya), but so far no study has described the bacterial communities of the glaciers in the Andes, the world’s longest mountain range. In this study, we describe the bacterial communities of three small (< 2 km2) high-elevation (< 4200 … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 57 publications
0
4
0
Order By: Relevance
“…Alphaproteobacteria were mainly composed of the orders Rhizobiales (cryoconite holes 2.5 ± 0.9%; ice 1.0 ± 0.3%, sediment 0.88%) and Sphingomonadales (cryoconite holes 2.2 ± 0.6%; ice 1.2 ± 0.4%, sediment 4.4%), which have been previously detected on other glaciers. 57–59 The order Sphingomonadales is known for its ability to degrade a wide range of aromatic hydrocarbons, particularly PAHs. 60 Differences between samples were also seen in their eukaryotic composition.…”
Section: Resultsmentioning
confidence: 99%
“…Alphaproteobacteria were mainly composed of the orders Rhizobiales (cryoconite holes 2.5 ± 0.9%; ice 1.0 ± 0.3%, sediment 0.88%) and Sphingomonadales (cryoconite holes 2.2 ± 0.6%; ice 1.2 ± 0.4%, sediment 4.4%), which have been previously detected on other glaciers. 57–59 The order Sphingomonadales is known for its ability to degrade a wide range of aromatic hydrocarbons, particularly PAHs. 60 Differences between samples were also seen in their eukaryotic composition.…”
Section: Resultsmentioning
confidence: 99%
“…The focus of our research was to study and compare the composition of cryoconite prokaryotic communities from remote regions across the globe, and to connect their variation with the chemical parameters of the sediment material. The studies on cryoconite microbiomes are limited by their inaccessibility and are mostly focused on the Arctic and Antarctic regions, and several mountain ridges, including Alps 7 , 8 , 11 and Andes 29 , while information on other regions is scarce 58 . Here, along with these locations, sampling sites introduced glaciers from the poorly covered areas of Northern Ural and Central Caucasus Mountains.…”
Section: Discussionmentioning
confidence: 99%
“…Some of the works cover the Andes 29 , the results of which showed that bacterial communities in cryoconites of South American glaciers were similar to those observed on other continents but they have fewer percentages of Cyanobacteria. They also revealed the linkage of the cryoconite bacterial community composition differences with geographical isolation and chemical characteristics of the substrate.…”
Section: Introductionmentioning
confidence: 86%
See 1 more Smart Citation